Diagnoses and key for the larvae of Progomphus Selys, 1854 from Argentina (Anisoptera: Gomphidae), with first larval descriptions for P. aberrans Belle, 1973 and P. kimminsi Belle, 1973 - Molineri, Carlos; Rodríguez, José Sebastián; Leiva, Marta; Márquez, Javier Andrés (Zootaxa, 2023)
Ten species of Progomphus Selys, 1854 are known to occur in Argentina. The larval stages of only four of them are described. We here add the larval descriptions of two species: P. aberrans Belle, 1973 and P. kimminsi Belle, 1973, and diagnose and illustrate important characters for the remaining species known at the larval stage in Argentina: P. complicatus Selys, 1854, P. joergenseni Ris, 1908, P. lepidus Ris, 1911 and P. phyllochromus Ris, 1918. New geographical records for these species are presented, including new records for P. kimminsi in Bolivia, and new provincial records in Argentina: P. aberrans and P. joergenseni in San Luis, and P. kimminsi in Santiago del Estero. A key to distinguish the larval stage of Argentinean species is proposed.